Nonlinear Dynamic Characteristics of PZT/Polymer Gripper. Issue 1 (January 2018) - Xu, Jia; Li, Yi-Ran; Wang, Hai-Bo; Zhu, Zhi-Wen
A kind of PZT/polymer gripper is proposed in this paper and its nonlinear dynamic response in bounded noise is described. In this paper, a polymer piezoelectric material is applied in gripper to substitute the traditional PZT to improve the response range. Nonlinear differential items are introduced to interpret the hysteretic phenomena of the PZT/polymer piezoelectric composites material, and the nonlinear dynamic model of the PZT/polymer gripper in bounded noise is developed. The dynamic response of the system is obtained, and the bifurcation characteristics of the system are analyzed. The results of numerical simulation and experiments show that the stochastic noise intensity has important influence on the system's dynamical response, and the stochastic resonance phenomenon occurs with the stochastic noise intensity variety.